If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 1y = 94 Solving 12x + 1y = 94 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 12x + 1y + -1y = 94 + -1y Combine like terms: 1y + -1y = 0 12x + 0 = 94 + -1y 12x = 94 + -1y Divide each side by '12'. x = 7.833333333 + -0.08333333333y Simplifying x = 7.833333333 + -0.08333333333y
| -200+25(4)= | | 6(2z+3)=-54 | | -200+25(2)= | | -(9x-8)=-5(3x-10) | | 3b-(b+2)=5-(3-b) | | (4y+3)=(y-2) | | 21x-5=7+15y | | 7(6x+10)=280 | | 9a^2(-5a^3+5a-5)= | | 4-8a=4(1-2a) | | 4sin^2(x)=2 | | 3g+5=7b-7.4 | | .35x+.30x=22.75 | | 8(n+6)+8=7n | | .35x+.30x=2275 | | -20=5x+5x+10 | | 9z=40500 | | -x-4=7x-68 | | (3p-7)=(5p-6) | | 10-6x+3x=-2 | | 29=76-46 | | 2(n+2)=5-5n | | 720=12x+100 | | -3n^5(5n+4)= | | 5m+6+4(3m-5)-5(m+5)=0 | | 7x+-4=1x+32 | | 12n+2(n-3)=1+5(2n-1) | | 12x+11y=18 | | 4b+3-b=4(b-5)+2 | | 0.4(p+1)-0.9(p+5)=-2 | | (2x^2+3x-6)-(x^2-18x+6)= | | -250+5(5)= |